The establishment and development of a system of physical training in Kazakhstan army - Nikiforov, Alekszander Viktorovics; Mukhamejanova, Sairan Sh. (Neveléstudomány | Oktatás – Kutatás – Innováció, 2017)
The paper describes the stages and chronology of physical training system development in the Republic of Kazakhstan Army. Close connection between the system of physical training and the development of the armed forces of the Republic of Kazakhstan was shown. Also, the opinion on the nature and organization/management of physical training changes with time, depending on the development of the country's military doctrine. The main stages of physical training system development were determined on the basis of the appropriate regulatory documents analysis.